TRADISI MEREAMI BAGI ETNIS BUTON DI DESA BUBU KECAMATAN KAMBOWA KABUPATEN BUTON UTARA - Yuslan Irawan; sitti hermina (SANGIA: Jurnal Penelitian Arkeologi, 2019)
The purpose of this research is to find out and describe the process of implementing the tradition ofreforming, as well as analyzing the symbolic meaning contained in the tradition of reforming. The location of thisresearch is Bubu Village, Kambowa District, North Buton Regency. Determination of informants using purposivesampling technique. Data collection is done through direct observation, in-depth interviews and documentation.Data analysis is carried out in a description through three channels, namely, data reduction, data presentationand conclusion drawing. The results of this study indicate that the tradition of reforming is a tradition intended forpeople who have just had a new vehicle, in the hope that the vehicle can avoid bad things, besides this traditionaims to express gratitude because it has a vehicle and hopes that the fortune will always delegated. There arethree stages in the process of implementing the tradition of reami, namely the initial stages of preparationincluding the mecalentu procession (determining mari good) and the procession of medambai (cooking). Theimplementation stage includes a procession of accusing chickens, chicken slaughter processions, and chickenblood sprinkling processions. The final stage of the haroa included the priest burning incense, reading thecongratulatory prayer, and finally eating together. The symbolic meaning contained in the reami tradition isdivided into two: symbolic meanings of equipment including the meaning of rice, money and eggs, the meaningof fruits, the meaning of native chicken, the meaning of chicken blood, the meaning of incense (comfort), themeaning of rice one plate and eggs 1 seed in gutters . The symbolic meaning of behavior includes the meaningof the day (determination of the day), the meaning of the implementation of reami in the morning, the meaning ofcleaning parts of chicken as much as 3 times and the meaning of raising the sun rising when slaughtering chickens.